Cultural Branding, Geographic Source Indicators and Commodification. (March 2016) - Hull, Gordon
One strategy for indigenous producers competing with global capital is to obtain geographic source protection (a form of trademark) for products traditionally associated with a cultural grouping or region. The strategy is controversial, and this article adds an additional reason to be cautious about adopting it. Specifically, consumers increasingly consume brands not for the products they designate but for the affiliation with the brands themselves. Since the benefits of source protection depend upon a consumer's desire to have a product actually from that source community, if consumers care more about the brand designation than the actual source, then those benefits will be more difficult to realize. In such an environment there would be tremendous pressure both to produce products that conform to (often exoticized) western images of cultures and to create property rights in the culture itself, empowering elites to further marginalize and suppress dissenting views.